Role of metabolic syndrome and lifestyle factors in endometrial cancer risk and prevention - Kwiatkowska, Anita; Małek, Natalia; Emerla, Sara; Brożyna, Aleksandra; Bydliński, Arkadiusz; Karłowicz, Konrad; Hermanowska, Maria; Lubomirska, Julia; Figurowska, Patrycja; Ciulkiewicz, Łukasz (Quality in Sport, 2024)
Introduction: The incidence of endometrial cancer, the sixth most common cancer among women, has been rising, especially in developed countries, possibly due to the obesity and diabetes pandemic. The aim of this review is to investigate the connection between metabolic syndrome, its individual components and endometrial cancer risk and to explore the role of lifestyle factors in endometrial cancer prevention. Materials and methods: For this review, we included studies regarding endometrial cancer and metabolic syndrome, obesity, diabetes and hyperglycemia, hypertension, dyslipidemia and several lifestyle factors, from 1994 to 2024. State of knowledge: This paper reviews existing literature on the relationship between metabolic syndrome and endometrial cancer, highlighting the significant role of central obesity, hyperglycemia and diabetes, dyslipidemia, and hypertension as risk factors. Evidence consistently demonstrates that individuals with metabolic syndrome, and its components individually, are at a heightened risk of developing endometrial cancer compared to those without metabolic abnormalities. Biological mechanisms linking metabolic syndrome’s components to endometrial cancer involve complex interplays between metabolic, hormonal or inflammatory factors and signalling pathways. Lifestyle interventions focusing on weight management, physical activity, and eating habits play an important role in reducing endometrial cancer risk and improving overall health outcomes. Conclusion: An understanding of the relationship between metabolic syndrome and endometrial cancer is crucial for improving risk stratification, early detection, and prevention strategies. Addressing metabolic abnormalities and promoting healthy lifestyle behaviours are essential actions against the rising incidence and burden of endometrial cancer.